2017
DOI: 10.1038/s41408-017-0035-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for arterial versus venous thrombosis in polycythemia vera: a single center experience in 587 patients

Abstract: In a recent International Working Group on Myeloproliferative Neoplasms Research and Treatment (IWG-MRT) study, prior arterial events and hypertension were predictors of subsequent arterial thrombosis whereas prior venous events and age ≥65 years predicted venous thrombosis in polycythemia vera (PV). In the current study, we sought to validate the above findings and identify additional predictors of arterial versus venous thrombosis. At a median follow up of 109 months, thrombosis after diagnosis occurred in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 15 publications
4
82
3
1
Order By: Relevance
“…There is considerable published evidence of an association between increased WBC count and thrombosis risk in PV (Barbui et al , ; Caramazza et al , ) ((De Stefano et al , ; Barbui et al , ) (Cerquozzi et al , ). In contrast, one prospective study did not find such an association (Passamonti et al , ).…”
Section: Platelet and Leucocyte Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…There is considerable published evidence of an association between increased WBC count and thrombosis risk in PV (Barbui et al , ; Caramazza et al , ) ((De Stefano et al , ; Barbui et al , ) (Cerquozzi et al , ). In contrast, one prospective study did not find such an association (Passamonti et al , ).…”
Section: Platelet and Leucocyte Targetmentioning
confidence: 99%
“…Abnormal karyotype and other molecular abnormalities (e.g. TET2 mutations) have been reported in PV and some may have prognostic value (Delic et al, 2016;Cerquozzi et al, 2017) but these tests are not routinely required at diagnosis.…”
Section: Role Of the Bone Marrow Biopsy In Jak2 V617f-positive Patientsmentioning
confidence: 99%
“…11 Â10 9 /L (hazard ratio, 1.3; 95% CI, 0.9-2.0; P ¼ .03) were associated with an increased risk of future TEs. 5 In the ECLAP study, a significant risk of major thrombosis was observed with a WBC count > 15 Â10 9 /L compared with a WBC count of 10 Â10 9 /L (hazard ratio, 1.71; 95% CI, 1.10-2.65; P ¼ .017). 3 These findings suggest that control of the WBC count should be an important consideration in the disease management in PV.…”
Section: Discussionmentioning
confidence: 97%
“…Arterial or venous thromboses are the most frequent complications in ET. Multiple risk factors of thrombosis including age, history of thrombosis, cardiovascular risks (eg, diabetes, hypertension, tobacco smoking), leucocytosis, the presence of JAK2V617F mutation and its allele burden have been recently identified …”
Section: Introductionmentioning
confidence: 99%
“…Multiple risk factors of thrombosis including age, history of thrombosis, cardiovascular risks (eg, diabetes, hypertension, tobacco smoking), leucocytosis, the presence of JAK2V617F mutation and its allele burden have been recently identified. 1,2 Even though approximately 50% of newly diagnosed ET patients are asymptomatic, some symptoms such as pruritus are commonly reported. We recently reported that like polycythemia vera (PV) patients, ET patients suffer from aquagenic pruritus (AP), an annoying pruritus that arises after contact with water and demonstrated some interesting clinical differences between MPN subtypes, particularly between PV and ET as the influence of water temperature, the duration and location of crises, and the influence of cytoreductive treatments.…”
Section: Introductionmentioning
confidence: 99%